Business process management : Blockchain and Robotic Process Automation Forum : BPM 2020 Blockchain and RPA Forum, Seville, Spain, September 13-18, 2020 : proceedings /: Blockchain and Robotic Process Automation Forum : BPM 2020 Blockchain and RPA Forum, Seville, Spain, September 13-18, 2020 : proceedings. ([2020]) - Unknown
No abstract available